Subjective Vs Objective Clinical Tools for Balance Assessment in Healthy Population - Reema Altaf, Sidra Hanif, Arooj Zameer, Aneek Kayani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The clinicians prefer subjective tools for balance assessment that are easily available and multiple researches have proved them reliable and valid for balance assessment. The force plate measures do the same postural analysis as we expect the other subjective tools to perform. Objectives: To determine the correlation between subjective and objective standard tools of balance assessment in healthy population Material and method: It was cross sectional observational study carried out at National institute of rehabilitation medicine (NIRM) Islamabad and Riphah international university Islamabad from January 2019 to June 2019.The sample size was calculated by using G power analysis graph, came out to be 64 for every age group. In this study non-probability purposive sampling technique was used. The inclusion criterion includes healthy individuals with 18-70 years of age (young (18-25 years), adult (25 -50 years), elderly (50-70 years) and both genders. Tools used in this research were BBS (Berg Balance Scale), POMA (The Performance-Oriented Mobility), TUG (Time Up and Go test), FRT (Functional Reach Test), Romberg test, SLS (Single Leg Stance), YBT (Y Balance Test) and Force plate. Results: 192 total respondents were divided in equal distribution of 64 in three age groups of elderly, adults and young. In elderly group males were 49and females were 15. In adult group males were 27 while females were 37.In young category total number of males were 27while females were 37. Mean age and SD for elderly, adults and young were 57.3±5.51, 35.4±6.97 and 22.6±1.62 respectively. This study results were affirming the fact that force plate variables has significant correlations with subjective tools of balance. (YBT, r=0.3 and SLS, r=0.8). Conclusion: This study concludes that force plate can replace or validate the subjective tools of balance that we use for different age groups. SLS (Single Leg Stance) is strongly and positively correlates with total AP sway on force plate, and shows strong negative correlation with AP standard deviation. YBT (Y-balance test) can also be validated or replaced for Total ML sway of force plate as it shows moderate correlation. On the other hand POMA, TUG, FRT shows weak and negative correlations with most of the force plate variables. Keywords: BBS (berg balance scale), ML (mediolateral), SD (standard deviation), YBT (Y-balance test)